Alumni from the Polytechnic of Leiria: path & challenges - Seco, Graça; Beato, Isabel; Duarte, Ângela (ICAReAlumni Conference Proceedings, 2019)
In this communication we will analyse the development of the Alumni Network of Polytechnic of Leiria, a higher public education institution in Portugal. The Alumni Network of Polytechnic of Leiria was constituted in February of 2012 with the aim to recover alumni relations, facilitating interactions, promoting the sharing of experiences and reinforcing the Institution’s recognition/image, empowering the long life learning, the information and knowledge updates and the reinforcement of an oriented community for the scientific and technological production. The Institution has around 12,000 current students and we estimate that 40,000 have finished their courses, short cycle’s, undergraduates and master’s degrees. The network has more than 4,000 registered alumni. In LinkedIn there are 13,500 former students connected and in Facebook there are more than 7,000 alumni following the page. This network develops activities towards former students such as: walk gatherings; anniversary cards; alumni days; the publishing of conferences, seminars, program offers; direct invitation to be a speaker; testimony collection; and alumni passport. The alumni passport is the official document sent to all alumni when they register that grants special conditions like access to canteens/bars and libraries; participation with special discount in events, conferences, courses and discounts in enterprises with an agreement with Polytechnic of Leiria. The testimony collection (flyers, videos) is also a great moment in the network since all the community can see the experiences before and after the alumni attended their school. The former students report their memories as resident students and the importance of the training received, presenting suggestions for the network life. Actually most of the activities are developed with the involvement and collaboration of current students who implement marketing strategies, creativity and new work tools to engage alumni. We regularly publish the initiatives/enterprises of our alumni and the prizes obtained. This is very courageous for them and we let all of the community know what they are doing, enabling them to be proud. This is also a way to inspire the current and future students. This is also a way to give visibility to the Institution which sees its reputation spread. Alumni of this initiative are also promotors of employment and are willing to recruit students from the same Institution. The mentors/ambassadors living in the country or even abroad are well engage to help other students. We are proud with the network development but conscious that a long way is waiting ahead, regarding the bigger involvement needed from the internal academic community if we want to reach volunteering and fundraise, another dimension of alumni relations and to proceed the alumni potential.